Risk factors for mortality among adult HIV/AIDS patients following antiretroviral therapy in Southwestern Ethiopia : an assessment through survival models - Seyoum, D.; Degryse, J. (MDPI, 2017)
Introduction: Efforts have been made to reduce HIV/AIDS-related mortality by delivering antiretroviral therapy (ART) treatment. However, HIV patients in resource-poor settings are still dying, even if they are on ART treatment. This study aimed to explore the factors associated with HIV/AIDS-related mortality in Southwestern Ethiopia. Method: A non-concurrent retrospective cohortstudywhichcollecteddatafromtheclinicalrecordsofadultHIV/AIDSpatients,whoinitiated ART treatment and were followed between January 2006 and December 2010, was conducted, to explore the factors associated with HIV/AIDS-related mortality at Jimma University Specialized Hospital (JUSH). Survival times (i.e., the time from the onset of ART treatment to the death or censoring) and different characteristics of patients were retrospectively examined. A best-ﬁt model waschosenforthesurvivaldata,afterthecomparisonbetweennativesemi-parametricCoxregression and parametric survival models (i.e., exponential, Weibull, and log-logistic). Result: A total of 456 HIV patients were included in the study, mostly females (312, 68.4%), with a median age of 30years(inter-quartilerange(IQR):23–37years). Estimatedfollow-upuntilDecember2010accounted for 1245 person-years at risk (PYAR) and resulted in 66 (14.5%) deaths and 390 censored individuals, representing a median survival time of 34.0 months ( IQR: 22.8–42.0 months). The overall mortality rate was 5.3/100 PYAR: 6.5/100 PYAR for males and 4.8/100 PYAR for females. The Weibull survival modelwasthebestmodelforﬁttingthedata(lowestAIC).Themainfactorsassociatedwithmortality were: baseline age (>35 years old, AHR = 3.8, 95% CI: 1.6–9.1), baseline weight (AHR = 0.93, 95% CI: 0.90–0.97),baselineWHOstageIV(AHR=6.2,95%CI:2.2–14.2),andlowadherencetoARTtreatment (AHR = 4.2, 95% CI: 2.5–7.1). Conclusion: An effective reduction in HIV/AIDS mortality could be achieved through timely ART treatment onset and maintaining high levels of treatment adherence
Journal article published in  International Journal of Environmental Research and Public Health · March 2017
Keywords: HIV/AIDS; Parametric survival model; Ethiopia; Antiretroviral therapy (ART); HIV-positive persons; AIDS (Disease) -- Patients; Highly active antiretroviral therapy